Species composition and bathymetric distribution of gorgonians (Anthozoa: Octocorallia) on the Southern Mexican Pacific coast - Rosalinda Abeytia; Héctor M. Guzmán; Odalisca Breedy (Revista de Biología Tropical, 2013)
Gorgonians are important components of coastal ecosystems, as they provide niches, natural compounds with medical applications and are used as bioindicators. Species composition and assemblage structure of gorgonians (Anthozoa: Octocorallia) were studied along a bathymetric profile in the Southern Mexican Pacific coast. Species composition was based on specimens collected within a depth range of 0-70m in 15 sites. The relative abundance of species was determined in six sites at four depths (5, 10, 20 and 25m) using three 10m2 transects at each depth level. Twenty-seven species of gorgonians belonging to six genera and three families were registered. The species composition varied with depth: 11 species were distributed between 0-25m depth, while 17 species were found between 40-70m depth interval. The shallow zone is characterized by a relatively large abundance of gorgonians, dominated by colonies of Leptogorgia cuspidata and L. ena. In contrast, the deepest zone was characterized by relatively low abundance of gorgonians, dominated by L. alba, the only species observed in both depth intervals. The similarity analysis showed differences in the composition and abundance of species by depth and site, suggesting that the main factor in determining the assemblage structure is depth. Results of this study suggest that the highest richness of gorgonian species in the study area may be located at depths of 40-70m, whereas the highest abundances are found between 5 and 10m depth. This study represents a contribution to the poorly known eastern Pacific gorgonian biota.